Bone marrow pathology in essential thrombocythemia: interobserver reliability and utility for identifying disease subtypes. - Wilkins, B; Erber, W; Bareford, D; Buck, G; Wheatley, K; East, C; Paul, B; Harrison, C; Green, A; Campbell, P (2008)
The role of histopathology in the diagnosis of essential thrombocythemia (ET) is controversial, and there has been little attempt to quantitate interobserver variability. Diagnostic bone marrow trephine biopsy specimens from 370 patients with ET by Polycythemia Vera Study Group (PVSG) criteria were assessed by 3 experienced hematopathologists for 16 different morphologic features and overall diagnosis according to the World Health Organization (WHO) classification. Our results show substantial interobserver variability, particularly for overall diagnosis and individual cellular characteristics such as megakaryocyte morphology. Reticulin grade was the dominant independent predictor of WHO diagnostic category for all 3 hematopathologists. Factor analysis identified 3 independent factors likely to reflect underlying biologic processes. One factor related to overall and lineage-specific cellularity and was significantly associated with JAK2 V617F status (P < .001), a second factor related to megakaryocyte clustering, and a third was associated with the fibrotic process. No differences could be discerned between patients labeled as having "prefibrotic myelofibrosis" or "true ET" in clinical and laboratory features at presentation, JAK2 status, survival, thrombosis, major hemorrhage, or myelofibrotic transformation. These results show that histologic criteria described in the WHO classification are difficult to apply reproducibly and question the validity of distinguishing true ET from prefibrotic myelofibrosis on the basis of subjective morphologic criteria. This study was registered at http://isrctn.org as #72251782 and at http://eudract.emea.europa.eu/ as #2004-000245-38.